A THIRD WAY: ONLINE LABS INTEGRATED WITH PRINT MATERIALS - Falmer, Roger (Indonesian Journal of Applied Linguistics, 2012)
Abstract: The use of ICT in language education to enhance classroom-based instruction is examined in reference to blended learning. A blended model of integrating technological advances via an online lab with a face-to-face classroom environment is presented. The example of this operating in practice is iZone, a four-level print-digital series designed with the online component called MyiZoneLab at its heart, forming a cohesive and inseparable whole with its accompanying texts. Overcoming the limitations of classroom-only instruction is a particular strength of advances in computer technology. Delivering a unified body of content through different mediums is in effect a third way, neither just online nor simply in class, and this newer model has the capability to fully exploit and reinforce the advantages of each separate medium. Online access via a web browser may make good on the promise of studying whenever the learner desires, wherever they happen to be. To this movement towards flexibility in time and place is added a further ingredient, that of choice in self-study or learning with others, and of matching the time the individual spends on tasks to their needs. Integration and inseparability are inherent in this blended model, unleashing the potentiality of technological developments in language education while seeking to transcend the either online or face-to-face learning dichotomy.Keywords: ICT (Information and Communications Technology), blended learning; online labs, F2F (face-to-face), integration